Community Empowerment Based on the Utilization and Preservation of Curcuma Caesea As a Local Superior Family Medicinal Plant - Bustami, Koko; Saifrizal, Muhammad; Simahatie, Mai; Maulana, Mizan; Juanda, Juanda; Silvina, Tika (Aceh Journal of Community Engagement (AJCE), 2025)
This activity was carried out to embrace and empower the community, especially farmers in Sido Mulyo Village, Kuta Makmur District, North Aceh Regency. Which then requires assistance in cultivating medicinal plants, namely curcuma ceasera (black turmeric) to make it easier to cultivate the plant. In addition, it also provides an understanding in order to get good and maximum production results. Partners of community service activities, both individuals and groups, institutions or agencies, expand their networks through the dissemination of information to social media, so that the location of the activity can be compared as a center for medicinal plant conservation, an education center and a center for developing community-based medicinal plant businesses. For its sustainability, support and assistance are needed in the process. Provision of funds or a place to open a herbal medicine shop is the final target in building a post-harvest business.